2011
DOI: 10.1177/1350650111406635
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic approach to water lubrication with biomolecular additives

Abstract: The aim of this study is to find a connection between mechanical engineering and biotechnology by utilizing biomimetics in lubrication. The objective is to improve boundary lubrication by biomolecules in water-based systems. Proteins were used because they can form films and multilayers on the surfaces and thus prevent direct contact between them. In this study, hydrophobin and albumin proteins are studied as additives to enable water lubrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…12,14 It has been observed that hydrophobins are able to reduce friction and wear of stainless steel surfaces when compared to water or buffer solutions without any additive molecules. Hydrophobins are small globular (diameter, y3 nm) amphiphilic proteins that are known to have a high tendency to adhere to surfaces and interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14 It has been observed that hydrophobins are able to reduce friction and wear of stainless steel surfaces when compared to water or buffer solutions without any additive molecules. Hydrophobins are small globular (diameter, y3 nm) amphiphilic proteins that are known to have a high tendency to adhere to surfaces and interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One additive type that can be used to enhance the lubrication properties of water is biomolecules. [11][12][13][14] In nature, biomolecules, such as proteins, phospholipids and carbohydrates, are used to form lubricating systems with friction coefficients as low as 0?001. 15 Some of these molecules have been successfully applied as lubricants on artificial surfaces and engineering materials 16,17 under relatively low contact pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, plastic shear of the surface asperities is fairly probable for the two hard tribopairs, POM-POM and steel-glass. According to Greenwood and Williamson [35], for an exponential asperity distribution, (3) where E′, σ, H and Rasp is the reduced Young's modulus, the roughness, the hardness and the average asperity radius of tribopair (for dissimilar material tribocontact, σ, H and Rasp of the softer material from the two materials in contact are used in the equation), a dimensionless plasticity index (ψ) can be introduced as a guideline for plastic shear of surface asperities; the contact will be elastic if ψ < ~0.69 and plastic (or fracture for brittle materials) if ψ > ~0.69. It is noted that ψ is independent of load.…”
Section: Hard Interfacesmentioning
confidence: 99%
“…Lubrication is not an exception; extensive efforts to utilize the principles of biological lubrication for man-made, engineering tribosystems have been put forth in the past a couple of decades [1][2][3]. One of the instrumental approaches in this endeavor is to use water as base lubricant [1][2][3][4][5], mimicking, for example, life-long maintenance of synovial joints of human and animals [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Penttilä, Nakari-Setälä, Rouvinen, Ritva, Sarlin, Serimaa, Szilvay, Askolin, Hakanpaa, Paananen, Kisko, etc.) also execute many projects about hydrophobins from the field [97] to the real products [98][99][100][101]. They have carried out many projects about genetic modification.…”
Section: Vtt Technical Research Centre Of Finlandmentioning
confidence: 99%